Digital-Based Madrasas: Approaches to Improve the Performance Quality of Madrasah Ibtidaiyah - Tomi Hamdani Siregar; Sri Hairani Pohan (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study investigates the internal and external factors influencing the improvement of digital-based performance quality in Madrasah Ibtidaiyah located in Tanjung Balai Municipality, North Sumatra, Indonesia. Employing a descriptive-analytical approach, the research utilized field data collected through observation, interviews, and documentation. The Internal Factor eval__uation (IFE), External Factor eval__uation (EFE), and Internal-External (IE) matrices were applied to analyze the data comprehensively. The results reveal that the three Madrasah Ibtidaiyah under study possess strong internal capabilities—particularly in leadership, human resources, and digital initiative implementation—that outweigh their identified weaknesses. Externally, these schools demonstrate significant adaptability to dynamic environmental conditions and exhibit strategic responsiveness that allows them to leverage existing opportunities, despite external constraints such as limited infrastructure and digital disparities. A SWOT analysis was conducted to formulate strategic alternatives, leading to the recommendation of an intensive strategy that combines market penetration—through the use of data analytics to strengthen digital-based educational services—and product development, especially in administrative and financial management systems. These strategic initiatives are expected to enhance the professionalism of educational personnel and improve institutional performance. The findings offer practical implications for policymakers and educational leaders committed to advancing the digital transformation of Islamic primary education